Une écologie symbolique totonaque. Le municipe de Huehuetla (Puebla, Mexique) - Nicolas Ellison (Journal de la Société des Américanistes)
A symbolic ecology of the Totonacs. The municipio of Huehuetla (Puebla, Mexico). This paper shows how, in the present context of ecological change and regional interethnic tensions, cosmological representations and especially forest symbolism find a new meaning in the contrast between Totonac found Mestizo use of the environment. Totonac found their identity on their special relation with wooded or agro-forestry areas, using a hot/cold classificatory system. Scholars have often focused on this dualistic principle in therapeutic and culinary practices, but its application at the level of symbolic classification of ecological spaces has rarely been studied in the Mesoamerican area.